Faktor - Faktor Yang Mempengaruhi Penggunaan Alat Kontrasepsi IUD oleh Pasangan Usia Subur di Wilayah Kerja Puskesmas Lubuk Begalung Padang - Rini Febrianti (STIKes Karsa Husada Garut, 2017)
IUD contraceptive use in Indonesia as much as 11%, in the province of West Sumatra as much as 9.74% in the whole city of Padang as much as 10.1%, in Puskesmas Lubuk Begalung a health center with a number of EFA as many as 11 379, which uses sebanyak156 IUD intrauterine device (2, 4%). The research objective was to determine the factors that affect the use of contraceptive IUD by spouses of fertile age in Puskesmas Padang Lubuk Begalung 2015. This study is an analytic with case control design using retrospective approach. This study was conducted on October 2015 to Januari 2016. The population of 156 people, how sampling simple random sampling, a total sample of 29 people, with a comparison of cases (EFA using contraceptives IUD) and control (EFA that do not use the IUD ) as many as 1: 1 is 58 people. Data were analyzed using univariate and bivariate analysis were then tested test statistic Chi-square. The results showed that 39.7% of acceptors have low knowledge level, 62.1% of acceptors have a negative attitude, 63.8% akspetor not have the support of a husband. There is influence between the level of knowledge (p = 0.032, OR 3.9), attitude (p = 0.015, OR 4.7), and the support of her husband (p = 0.029, OR 4.10) with the use of IUD contraception by couples of childbearing age. It is concluded that the level of knowledge acceptor is still low, so as to influence the attitudes and support of a husband who would they get. Advice can be given is to the health center in order to make this study as a contribution in the improvement of health care information, and can also develop obstetrics